Fixed Ladder Safety: Summarizing OSHA Requirements - Serap Gorucu; Charles Brown; Carol Lehtola (EDIS)
This publication summarizes the parts of the OSHA Standard 1910.23 and 1910.28 that apply to fixed ladders. Written by Serap Gorucu, Charles Brown, and Carol Lehtola, and published by the UF/IFAS Department of Agricultural and Biological Engineering, April 2022.